Revisión de la teoría reflexiva del conocer humano - Sellés, Juan Fernando (Sapientia, 2013)
In this paper we examine the «reflexive theory» of human knowledge. After expose in sort his history, we summarize some variations that this hypothesis offers. We present the difficulties that suggest this opinion. A series of questions are established in each one of the human noethical levels in which are defended this supposition in order to demonstrate these problems.